2022
DOI: 10.1021/acsapm.2c01195
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating the Curing of Hybrid Poly(Hydroxy Urethane)-Epoxy Adhesives by the Thiol-Epoxy Chemistry

Abstract: The polyaddition between dicyclic carbonates and diamines leading to poly(hydroxy urethane)s (PHUs) has emerged as the preferred method for the synthesis of green, non-isocyanate polyurethanes. However, when proposed for use as structural adhesives, the long times for completion of aminolysis of the 5membered cyclic carbonates under ambient conditions force the use of complementary chemistries to accelerate the curing process. In this work, a system that combines an amino-terminated PHU (NH 2 −PHU−NH 2 ), an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The test results (Figure 4C) showed that the tensile strength of the samples after remolding once was 80 MPa, which was slightly lower than that of the original specimen (89 MPa). Excitingly, the tensile strength of the samples could still maintain 60 MPa after remolding twice, which is higher than the existing reported tensile strength of thiol‐epoxy thermoset materials 19,25–30 . This indicates that the EIA‐based epoxy thermoset material has excellent processability properties.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…The test results (Figure 4C) showed that the tensile strength of the samples after remolding once was 80 MPa, which was slightly lower than that of the original specimen (89 MPa). Excitingly, the tensile strength of the samples could still maintain 60 MPa after remolding twice, which is higher than the existing reported tensile strength of thiol‐epoxy thermoset materials 19,25–30 . This indicates that the EIA‐based epoxy thermoset material has excellent processability properties.…”
Section: Resultsmentioning
confidence: 69%
“…The glass transition temperature ( T g ) was determined by the peak tan δ of the DMA test, as shown in Figure 3B. The T g increased continuously with increasing BDB values and was as high as 105.2°C for EB7T3, which is higher than that reported by other researchers for thiol‐epoxy thermosets 19,25–30 . Compared with the existing reported literature, the EIA‐based epoxy thermosets with hybrid cross‐linked network structure had the highest tensile strength while maintaining high T g (Figure 3C).…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“… 14 The cohesive force in the PHUs was found to be dominant over the adhesive strength between the PHU and aluminum layer. Even though a few articles explored the applicability of PHUs as adhesives, the dicarbonates utilized for synthesizing these PHUs mainly depend on non‐renewable material and often involve further modifications or crosslinking to achieve better adhesive strength 46–51 …”
Section: Resultsmentioning
confidence: 99%